Calculating the inventory of an item with normal demand and exponential delivery time - Izar Landeta, Juan Manuel; Nájera Saldaña, José Adrián; Zárate Camacho, Lizbeth Angélica (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To study the case of calculating the inventory of an item with normal demand and exponential supplier delivery time. MATERIAL AND METHOD: Traditional order quantity and reorder point models are applied through simulation, including savings from purchasing larger volumes. RESULTS: The order quantity and reorder point were obtained for the illustrative case, and then the word-of-mouth effect and standard deviation of demand were varied. As these two parameters increase, so does inventory cost, with the change in cost being practically linear with the standard deviation. CONCLUSIONS: The order quantity was within the lower limits of maximum volume, 5,001 and 10,001 items. As the word-of-mouth effect increased, the cost of shortages and inventory, as well as the order quantity, increased. With a higher standard deviation, inventory costs increased linearly, even increasing the reorder point. Among the limitations of the study is that a probability distribution was used for the supplier’s demand and delivery time, which allows for the use of other probability distributions in future cases.